Effects of Overexpression of WRI1 and Hemoglobin Genes on the Seed Oil Content of Lepidium campestre - Ivarson, Emelie; Leiva-Eriksson, Nélida; Ahlman, Annelie; Kanagarajan, Selvaraju; Bülow, Leif; Zhu, Li-Hua (Frontiers in Plant Science, 2017)
The wild species field cress (Lepidium campestre), belonging to the Brassicacae family, has potential to be developed into a novel oilseed- and catch crop, however, the species needs to be further improved regarding some important agronomic traits. One of them is its low oil content which needs to be increased. As far as we know there is no study aiming at increasing the oil content that has been reported in this species. In order to investigate the possibility to increase the seed oil content in field cress, we have tried to introduce the Arabidopsis WRINKLED1 (AtWRI1) or hemoglobin (Hb) genes from either Arabidopsis thaliana (AtHb2) or Beta vulgaris (BvHb2) in field cress with the seed specific expression. The hypothesis was that the oil content would be increased by overexpressing these target genes. The results showed that the oil content was indeed increased by up to 29.9 %, 20.2 % and 25.9 % in the transgenic lines expressing AtWRI1, AtHb2 and BvHb2, respectively. The seed oil composition of the transgenic lines did not significantly deviate from the seed oil composition of the wildtype plants. Our results indicate that genetic modification can be used in this wild species for its fast domestication into a future economically viable oilseed- and catch crop.